Analisa Perawatan Mesin Pulper Menggunakan Metode Overall Equipment Effectiveness (OEE) - Ahlaq, Ade Mukhlis Shoutul; Cahyadi, Dadi; Handika, Firdanis Setyaning (Universitas Serang Raya, 2017)
This study aims to determine the effectiveness of Pulper machines. The research was conducted using the Overall Equipment Effectiveness method. The research conducted at a company engaged in the Pulp & Paper field. Data collected by interviews and conducting direct observations in the area during February 2017. Based on the research, it can conclude that the Pulley OEE value was obtained by 77.31% with the main factor causing damage was Broken Ragger by 46%. The proposed improvements that can be given to minimize the incidence of broken ragger are training of ragger machine operators regularly, planning maintenance of scheduled ragger machines as well as providing tools to make it easier for operators to repair damaged machines